Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Working memory processes and the histamine-3 receptor in schizophrenia: a [11C]MK-8278 PET-fMRI study - Atheeshaan Arumuham; Ekaterina Shatalina; Matthew M. Nour; Mattia Veronese; Ellis Chika Onwordi; Stephen J. Kaar; Sameer Jauhar; Eugenii A. Rabiner; Oliver D. Howes (Psychopharmacology, 2025)
Rationale Working memory impairment is a prominent feature of schizophrenia which predicts clinical and functional outcomes. Preclinical data suggest histamine-3 receptor (H3R) expression in cortical pyramidal neurons may have a role in working memory, and post-mortem data has found disruptions of H3R expression in schizophrenia. Objectives We examined the role of H3R in vivo to elucidate its role on working memory impairment in schizophrenia. Methods We used positron emission tomography (PET) with the selective H3R radioligand [ 11 C]MK-8278 to measure H3R availability, and employed a task during functional magnetic resonance imaging (fMRI) to assess working memory-evoked brain activation and cognitive task performance, in patients with schizophrenia ( n = 12) and matched healthy volunteers ( n = 12). We assessed the relationship between H3R availability and both task performance and working memory-evoked brain activation in regions of interest (ROIs), including the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). Results Patients with schizophrenia showed a strong positive correlation, after corrections for multiple comparisons, between ACC H3R availability and task performance (rho = 0.73, p = 0.007), which was absent in the control group (rho = 0.03, p = 0.94). Further ROI analysis did not find a significant relationship between H3R availability and working memory-evoked brain activation. Conclusions These results provide support for the role of H3R on working memory processes in patients with schizophrenia.

Emergency mass disposal of milk: Options and considerations - A. Mahdaviarab; K. Pahlavanyali; R. Cheng; X. Wang; J. Doria; J.A. Howe; J.M. Piñeiro; J. Spencer; Z. Liu (Journal of Environmental Management, 2025)

Brushite: a Reclaimed Phosphorus Fertilizer for Agricultural Nutrient Fertilization - Harrison R. Coker; Rui Yang; Isaiah J. Robertson; Joshua M. Doria; Katie L. Lewis; Julie A. Howe (Journal of Soil Science and Plant Nutrition, 2025)
Phosphorus fertilizers are typically produced from mined and chemically processed rock phosphate, which is a diminishing non-renewable resource. Wastewater-reclaimed phosphorus minerals, such as brushite (CaHPO 4 ·2H 2 O), have the potential to be utilized as agricultural fertilizers. The commercial recovery of brushite from wastewater processing is a recent advancement; however, its efficacy as an agricultural fertilizer has yet to be evaluated. Wastewater-reclaimed brushite was tested in a greenhouse and field setting. In the greenhouse study, two P-limited soils were used to grow corn fertilized using brushite and were compared with struvite (NH 4 MgPO 4 ·6H 2 O), another reclaimed P source, and conventional P fertilizers, triple super phosphate (TSP) and monoammonium phosphate (MAP). In the field, corn, wheat, and cotton were grown in two ecoregions for two sites years to compare brushite and struvite with conventional fertilizers. Plants were evaluated for P uptake and yield, and P availability was determined as extractable P. Results indicate that brushite promoted plant productivity similar to conventional fertilizers in P-limited greenhouse soils. Field studies demonstrated similar uptake and assimilation of brushite-P compared to synthetic fertilizers and struvite. Soil acidification occurred across all fertilization treatments. The use of reclaimed brushite as a P fertilizer appears to be as effective as commercially available synthetic fertilizers.

An Assessment of Demersal Elasmobranch Occurrence and Associated Habitats Using an Autonomous Underwater Vehicle ( AUV ) - Jonathon Taylor; John A. Howe; James Thorburn; Clive J. Fox; Christopher McGonigle; Petra Rybanska (Marine Ecology, 2025)
To implement effective management and conservation strategies, an understanding of the spatial ecology, habitat preferences and movement of demersal elasmobranchs is required. This study combines a photographic survey obtained from an autonomous underwater vehicle (AUV) with existing bathymetric data to help understand elasmobranch ecology within the Firth of Lorn, western Scotland. This area is within the Loch Sunart to Sound of Jura Marine Protected Area (MPA) and designated for the protection of the critically endangered flapper skate ( Dipturus intermedius ). Two areas of seabed were surveyed using an AUV in water depths of 110–165 m southwest of the Isle of Kerrera. Eight surveys were conducted in total, four in each area. Each area was surveyed twice over 2 days in October 2020 and twice in 2 days in May June 2021. One day used bait on the seabed (October) whilst all the others had no bait. For each survey, the AUV travelled 17 km at a height of 2 m above the seabed in a lawnmower pattern providing 0.5 km 2 photographic coverage for ~2 h per survey. Five elasmobranch species, two scyliorhinids ( Scyliohinus canicula and Galeus melastomus ) and three rajiformes ( D. intermedius , Raja clavata and Leucoraja naevus ), were identified from a total of 43 k seabed photographs. In total 42 individual animals and 7 egg cases were observed. Although the AUV had short survey times and small study areas the results are encouraging for AUVs being a useful tool in understanding elasmobranch ecology.

The role of ocean circulation and regolith removal in triggering the Mid-Pleistocene Transition: Insights from authigenic Nd isotopes - Thomas J. Williams; Alexander M. Piotrowski; Jacob N.W. Howe; Claus-Dieter Hillenbrand; Claire S. Allen; Josephine A. Clegg (Quaternary Science Reviews, 2024)

The unexpected influence of legacy conspecific density dependence - Lukas J. Magee; Joseph A. LaManna; Amy T. Wolf; Robert W. Howe; Yuanming Lu; Denis Valle; Daniel J. B. Smith; Robert Bagchi; David Bauman; Daniel J. Johnson (Ecology Letters, 2024)
When plants die, neighbours escape competition. Living conspecifics could disproportionately benefit because they are freed from negative intraspecific processes; however, if the negative effects of past conspecific neighbours persist, other species might be advantaged, and diversity might be maintained through legacy effects. We examined legacy effects in a mapped forest by modelling the survival of 37,212 trees of 23 species using four neighbourhood properties: living conspecific, living heterospecific, legacy conspecific (dead conspecifics) and legacy heterospecific densities. Legacy conspecific effects proved nearly four times stronger than living conspecific effects; changes in annual survival associated with legacy conspecific density were 1.5% greater than living conspecific effects. Over 90% of species were negatively impacted by legacy conspecific density, compared to 47% by living conspecific density. Our results emphasize that legacies of trees alter community dynamics, revealing that prior research may have underestimated the strength of density dependent interactions by not considering legacy effects.

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

A review of new and existing non-extractive techniques for monitoring marine protected areas - Ryan McGeady; Robert M. Runya; James S. G. Dooley; John A. Howe; Clive J. Fox; Andrew J. Wheeler; Gerard Summers; Alexander Callaway; Suzanne Beck; Louise S. Brown; Gerard Dooly; Chris McGonigle (Frontiers in Marine Science, 2023)
Ocean biodiversity loss is being driven by several anthropogenic threats and significant efforts are required to halt losses and promote healthy marine ecosystems. The establishment of a network of Marine Protected Areas (MPAs) can help restrict damaging activities and have been recognised as a potential solution to aid marine conservation. When managed correctly they can deliver both ecological and socio-economic benefits. In recent times, MPA designations have increased rapidly while many countries have set future MPA targets for the decades ahead. An integral element of MPA management is adequate monitoring that collects data to assess if conservation objectives are being achieved. Data acquired by monitoring can vary widely as can the techniques employed to collect such data. Ideally, non-destructive and non-invasive methods are preferred to prevent damage to habitats and species, though this may rule out a number of traditional extractive sampling approaches such as dredges and trawls. Moreover, advances in ocean observation technologies enable the collection of large amounts of data at high resolutions, while automated data processing is beginning to make analyses more logistically feasible and less time-consuming. Therefore, developments to existing marine monitoring techniques and new emerging technologies have led to a diverse array of options when choosing to implement an MPA monitoring programme. Here, we present a review of new and existing non-extractive techniques which can be applied to MPA monitoring. We summarise their capabilities, applications, advantages, limitations and possible future developments. The review is intended to aid MPA managers and researchers in determining the suitability of available monitoring techniques based on data requirements and site conditions.

Consumer feces impact coral health in guild-specific ways - Carsten G. B. Grupstra; Lauren I. Howe-Kerr; Jesse A. van der Meulen; Alex J. Veglia; Samantha R. Coy; Adrienne M. S. Correa (Frontiers in Marine Science, 2023)
Animal waste products are an important component of nutrient cycles and result in the trophic transmission of diverse microorganisms. There is growing recognition that the feces of consumers, such as predators, may impact resource species, their prey, via physical effects and/or microbial activity. We tested the effect of feces from distinct fish trophic groups on coral health and used heat-killed fecal controls to tease apart physical versus microbial effects of contact with fecal material. Fresh grazer/detritivore fish feces caused lesions more frequently on corals, and lesions were 4.2-fold larger than those from sterilized grazer/detritivore feces; in contrast, fresh corallivore feces did not cause more frequent or larger lesions than sterilized corallivore feces. Thus, microbial activity in grazer/detritivore feces, but not corallivore feces, was harmful to corals. Characterization of bacterial diversity in feces of 10 reef fish species, ranging from obligate corallivores to grazer/detritivores, indicated that our experimental findings may be broadly generalizable to consumer guild, since feces of some obligate corallivores contained ~2-fold higher relative abundances of coral mutualist bacteria ( e.g., Endozoicomonadaceae), and lower abundances of the coral pathogen, Vibrio coralliilyticus , than feces of some grazer/detritivores. These findings recontextualize the ecological roles of consumers on coral reefs: although grazer/detritivores support coral reef health in various ways ( e.g. , promoting coral settlement and herbivory through the removal of detritus and sediments from the algal matrix), they also disperse coral pathogens. Corallivore predation can wound corals, yet their feces contain potentially beneficial coral-associated bacteria, supporting the hypothesized role of consumers, and corallivores in particular, in coral symbiont dispersal. Such consumer-mediated microbial dispersal as demonstrated here has broad implications for environmental management.

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Historic and Modern Approaches for the Discovery of Abandoned Wells for Methane Emissions Mitigation in Oil Creek State Park, Pennsylvania - Patricia M. B. Saint-Vincent; James I. Sams; Mumbi Mundia-Howe; Matthew D. Reeder; Garret A. Veloski; Natalie J. Pekney (Environmental Management, 2021)

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Ecological drivers of spatial community dissimilarity, species replacement and species nestedness across temperate forests - Xugao Wang; Thorsten Wiegand; Kristina J. Anderson‐Teixeira; Norman A. Bourg; Zhanqing Hao; Robert Howe; Guangze Jin; David A. Orwig; Marko J. Spasojevic; Shunzhong Wang; Amy Wolf; Jonathan A. Myers (Global Ecology and Biogeography, 2018)
Aims Patterns of spatial community dissimilarity have inspired a large body of theory in ecology and biogeography. Yet key gaps remain in our understanding of the local‐scale ecological processes underlying species replacement and species nestedness, the two fundamental components of spatial community dissimilarity. Here, we examined the relative influence of dispersal limitation, habitat filtering and interspecific species interactions on local‐scale patterns of the replacement and nestedness components in eight stem‐mapped temperate forest mega‐plots at different ontogenetic stages (large versus small trees). Location Eight large (20–35 ha), fully mapped temperate forest plots in northern China and northern U.S.A. Time period 2004–2016. Major taxa studied Woody plants. Methods We combined decomposition of community dissimilarity (based on the Ružička index) and spatial point‐pattern analysis to compare the spatial (i.e., distance‐dependent) replacement and nestedness components of each plot with that expected under five spatially explicit null models representing different hypotheses on community‐assembly mechanisms. Results Our analyses revealed complex results. In all eight forests, spatial community dissimilarity was best explained by species replacement among local tree assemblages and by a null model based on dispersal limitation. In contrast, spatial nestedness for large and small trees was best explained by random placement and habitat filtering, respectively, in addition to dispersal limitation. However, interspecific interactions did not contribute to local replacement and nestedness. Main conclusions Species replacement is the predominant process accounting for spatial community dissimilarity in these temperate forests and caused largely by local‐scale species clustering associated with dispersal limitation. Nestedness, in contrast, is less prevalent and primarily associated with larger variation in local species richness as caused by spatial richness gradients or ‘hotspots’ of local species richness. The novel use of replacement and nestedness measures in point pattern analysis is a promising approach to assess local‐scale biodiversity patterns and to explore their causes.

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Photogrammetry of blue whales with an unmanned hexacopter - John W. Durban; Michael J. Moore; Gustavo Chiang; Leigh S. Hickmott; Alessandro Bocconcelli; Gloria Howes; Paulina A. Bahamonde; Wayne L. Perryman; Donald J. LeRoi (Marine Mammal Science, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Diversity of transcripts and transcript processing forms in plastids of the dinoflagellate alga Karenia mikimotoi - Richard G. Dorrell; George A. Hinksman; Christopher J. Howe (Plant Molecular Biology, 2016)

Comparative sensitivity of the cnidarian Exaiptasia pallida and a standard toxicity test suite: testing whole effluents intended for ocean disposal - P. L. Howe; A. J. Reichelt-Brushett; R. Krassoi; T. Micevska (Environmental Science and Pollution Research, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Conspecific negative density‐dependent mortality and the structure of temperate forests - Daniel J. Johnson; Norman A. Bourg; Robert Howe; William J. McShea; Amy Wolf; Keith Clay (Ecology, 2014)
Factors that control tree seedling dynamics are critical determinants of forest diversity. We examined the role of density‐dependent mortality and abiotic factors in the differential establishment and survival of tree seedlings at three, large, mapped forest plots in Indiana, Virginia, and Wisconsin, USA. We tested whether seedling densities and seedling survival are related to local biotic and abiotic factors with generalized linear mixed models. Spatial point pattern analyses were utilized to determine if the distribution patterns of seedlings and saplings are consistent with a pattern generated by negative density‐dependent mortality with respect to conspecific trees. Initial sampled seedling density for nearly a third of species showed a positive correlation with increasing conspecific basal area, indicating dispersal limitation, but few had any association with abiotic variables. By contrast, survival of seedlings over one year significantly declined with increasing conspecific basal area. Point pattern analyses indicated that nearly one‐third of tree species had significantly over‐dispersed point patterns of conspecific seedlings and saplings relative to adult densities; the majority of other species exhibited random spatial arrangements. Our results demonstrate that negative conspecific density‐dependent mortality of seedlings could generate the spatial patterns observed at later life stages. By differentially favoring seedlings of other species, this process may contribute to the maintenance of tree diversity in temperate forests, just as others have demonstrated for tropical forests.

The link between dopamine function and apathy in cannabis users: an [18F]-DOPA PET imaging study - Michael A. P. Bloomfield; Celia J. A. Morgan; Shitij Kapur; H. Valerie Curran; Oliver D. Howes (Psychopharmacology, 2014)

Coastal dune stabilization in Wales and requirements for rejuvenation - K. Pye; S. J. Blott; M. A. Howe (Journal of Coastal Conservation, 2014)

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Structural and kinetic studies of imidazole binding to two members of the cytochrome c 6 family reveal an important role for a conserved heme pocket residue - Badri S. Rajagopal; Michael T. Wilson; Derek S. Bendall; Christopher J. Howe; Jonathan A. R. Worrall (JBIC Journal of Biological Inorganic Chemistry, 2011)

Molecular mapping of adult plant stripe rust resistance in wheat and identification of pyramided QTL genotypes - H. S. Bariana; U. K. Bansal; A. Schmidt; A. Lehmensiek; J. Kaur; H. Miah; N. Howes; C. L. McIntyre (Euphytica, 2010)

Tissue stretch induces nuclear remodeling in connective tissue fibroblasts - Helene M. Langevin; Kirsten N. Storch; Robert R. Snapp; Nicole A. Bouffard; Gary J. Badger; Alan K. Howe; Douglas J. Taatjes (Histochemistry and Cell Biology, 2010)

Do estuaries pose a toxic contamination risk for wading birds? - J. T. Smith; L. A. Walker; R. F. Shore; S. E. A. le V. dit Durell; P. D. Howe; M. Taylor (Ecotoxicology, 2009)

Directional gene flow patterns in disjunct populations of the black ratsnake (Pantheropis obsoletus) and the Blanding’s turtle (Emydoidea blandingii) - Briar J. Howes; Joseph W. Brown; H. Lisle Gibbs; Tom B. Herman; Stephen W. Mockford; Kent A. Prior; Patrick J. Weatherhead (Conservation Genetics, 2009)

How spatially coherent and statistically robust are temporal changes in extreme precipitation in the contiguous USA? - S. C. Pryor; J. A. Howe; K. E. Kunkel (International Journal of Climatology, 2009)
Century‐long precipitation records from stations in the contiguous USA indicate an increased frequency of rainy days over the past century and some evolution in the probability distributions of precipitation amount. Temporal trends in eight metrics of the precipitation climate are of similar magnitude and sign regardless of whether they are derived from bootstrapping of regression residuals or using the Kendall's tau statistic, though the bootstrap technique generally resolved a larger number of ‘significant’ trends. There is substantial variability in terms of the magnitude, significance and sign of the linear trends with specific metrics, and they are sensitive to recording bias of light precipitation events in the early part of the 20th century. The majority of stations that exhibit significant linear trends show evidence of increases in the intensity of events above the 95th percentile. The resolved trends tend to have a larger magnitude at the end of the century. Spatial variability as manifest in the spatial autocorrelation in the interannual variability and trends in extreme metrics is manifest at a range of scales, but in general the correlation between stations is significant only for separation of distances of a few tens of kilometres. The largest trends towards increased annual total precipitation, number of rainy days and intense precipitation (e.g. fraction of precipitation derived from events in excess of the 90th percentile value) are focussed on the Central Plains/northwestern Midwest. Copyright © 2008 Royal Meteorological Society

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)

Growth Suppression of Canola Through Wheat Stubble I. Separating Physical and Biochemical Causes in the Field - S. E. Bruce; J. A. Kirkegaard; J. Pratley; G. Howe (Plant and Soil, 2006)

The use of cover crops in cereal-based cropping systems to control nitrate leaching in SE England - A. J. Macdonald; P. R. Poulton; M. T. Howe; K. W. T. Goulding; D. S. Powlson (Plant and Soil, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Highly variable SSR markers in Douglas-fir: Mendelian inheritance and map locations - G. T. Slavov; G. T. Howe; I. Yakovlev; K. J. Edwards; K. V. Krutovskii; G. A. Tuskan; J. E. Carlson; S. H. Strauss; W. T. Adams (Theoretical and Applied Genetics, 2004)

Expression of a Truncated Brca1 Protein Delays Lactational Mammary Development in Transgenic Mice - Melissa A. Brown; Hans Nicolai; Kathy Howe; Toyomasa Katagiri; El-Nasir Lalani; Kaylene J. Simpson; Nathan W. Manning; Andrew Deans; Phil Chen; Kum Kum Khanna; Mas Rina Wati; Beatrice L. Griffiths; et al. (Transgenic Research, 2002)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)

Design of a summary screen for an ICU patient data management system - R. H. Ireland; H. V. James; M. Howes; A. J. Wilson (Medical & Biological Engineering & Computing, 1997)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

Non-dietary factors as risk factors for breast cancer, and as effect modifiers of the association of fat intake and risk of breast cancer - David J. Hunter; Donna Spiegelman; Hans-Olov Adami; Piet A. van den Brandt; Aaron R. Folsom; R. Alexandra Goldbohm; Saxon Graham; Goeffrey R. Howe; Lawrence H. Kushi; James R. Marshall; Anthony B. Miller; Frank E. Speizer; et al. (Cancer Causes & Control, 1997)

Mouse leukaemia, a dichotomy of virus neutralizing and cytotoxic antibodies - J. G. Sinkovics; C. C. Shullenberger; C. D. Howe; Barbara A. Bertin (Archives of Virology, 1966)